Study of Polar Codes - Guesmia Rabeh; CHELLALI Safouane (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
The problem of information interference or damage during its transmission from the sender to the receiver is a problem with different stations, as the devices that deal with the information and the operations that occur to the information are different according to its position in the communication chain from the source to the transmission channel down to the receiver, during which the information is subject to encoding and decoding processes Encryption in order to protect it from damage and theft, and in this regard, the world Erdal Arıkan invented the Polar Code in 2008, as it provides us with two characteristics at the same time that works to protect the information and increase the capacity of the channel in order to send the largest possible number of bits At the same time
OPTION : Systèmes de Télécommunications